2000
DOI: 10.1128/iai.68.5.2797-2803.2000
|View full text |Cite
|
Sign up to set email alerts
|

Human Immune Responses toSchistosoma mansoniVaccine Candidate Antigens

Abstract: To determine the naturally occurring immunological responses to the Schistosoma mansoni antigens paramyosin, IrV-5, Sm-23 (MAP-3), and triose phosphate isomerase (MAP-4), a total of 119 subjects from an area of endemicity for schistosomiasis, including "resistant" subjects (n ‫؍‬ 17) were evaluated. Specific immunoglobulin G1 (IgG1), IgG2, IgG3, IgG4, and IgA levels for each of the antigens and the cytokine profile in culture supernatants from antigen-stimulated peripheral blood mononuclear cells (PBMC) were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 67 publications
2
63
0
2
Order By: Relevance
“…In addition, it plays a vital role in acquisition of host derived nutrients, including carbohydrates, amino acids, and lipids (Abath & Werkhauser 1996, Jones et al 2004. Along with other key molecules, tegument associated antigens of schistosomes have been investigated as targets of protective immune responses in murine hosts and for defining antibody and cytokine correlates of apparent resistance and susceptibility in human populations, a key approach to establishing the protective potential of a vaccine candidate (Ribeiro de Jesus et al 2000, Acosta et al 2002, Al-Sherbiny et al 2003, McManus & Bartley 2004, Bergquist et al 2005. Since SVLBP appears to have VLDL binding activity and to locate prominently on the tegument and sub-tegument of adult male schistosomes, SVLBP may play a key role in lipid acquisition by S. japonicum (Fan et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it plays a vital role in acquisition of host derived nutrients, including carbohydrates, amino acids, and lipids (Abath & Werkhauser 1996, Jones et al 2004. Along with other key molecules, tegument associated antigens of schistosomes have been investigated as targets of protective immune responses in murine hosts and for defining antibody and cytokine correlates of apparent resistance and susceptibility in human populations, a key approach to establishing the protective potential of a vaccine candidate (Ribeiro de Jesus et al 2000, Acosta et al 2002, Al-Sherbiny et al 2003, McManus & Bartley 2004, Bergquist et al 2005. Since SVLBP appears to have VLDL binding activity and to locate prominently on the tegument and sub-tegument of adult male schistosomes, SVLBP may play a key role in lipid acquisition by S. japonicum (Fan et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…S. mansoni paramyosin is strongly recognized by sera of individuals naturally resistant to infection and it also induced high levels of IFN-γ production by peripheral blood mononuclear cells (PBMC) from these individuals [11,12]. Paramyosin also induced significant lymphocyte proliferation and interleukin (IL-2) and IL-5 production in individuals resistant to S. mansoni reinfection [13].…”
Section: Introductionmentioning
confidence: 99%
“…PBMC of 14% of individuals in this study did not proliferate in response to paramyosin peptides (data not shown). Para (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) was the most promiscuous peptide according to the proliferative responses. PBMC from 20% of the individuals tested proliferated in response to this epitope ( Table 2).…”
Section: Cellular Immune Response To Paramyosin Synthetic Peptidesmentioning
confidence: 99%
“…In the liver, a male parasite will mate with a female and carry her to mesenteric or pelvic circulation, the final destination being parasite species specific (Wilson, 2009). It was shown that infection of humans with live, RA parasites led to strong protection against subsequent challenge infections with normal cercariae (Correa-Oliveira et al, 2000;Ribeiro de Jesus et al, 2000). Vaccination of animal models with RA cercariae has thus led to an adult worm burden reduction in experimental schistosomiasis of 60-70% (Bickle et al, 1979a,b; CauladaBenedetti et al, 1991;Coulson et al, 1998;McManus, 1999;Dillon et al, 2008).…”
Section: Prevention Of Schistosomiasisvaccinesmentioning
confidence: 99%